The Effect of Religious Conflicts in Northern Nigeria on Public Health Outcomes: A Case Study of Cholera Outbreak - Nuhu, Adamu; Yusuf, Kabir M. (European Scientific Journal, ESJ, 2018)
Violent conflicts, in most cases, pose an unquantifiable challenge to human health and health systems especially in developing countries. Complex humanitarian emergencies as a result of conflicts could severely have negative consequences on public health. Nigeria has faced series of threatening security challenges, but the one caused by the activities of the socalled Islamist sect, the Boko Haram (BH), remains protracted, especially in Borno, a State in the north-eastern part of the country. The resultant outcome is the internally displaced persons (IDPs) who have suffered from many diseases especially cholera, which has continued to ravage these displaced populations. Conflict can contribute to water shortage through the destruction of water sources, such as wells, reservoirs and laid pipes, and its contamination. This is happening on an already weak health system. Though cholera is easily treatable, concerted efforts by government and medical humanitarian agencies are urgently required to ameliorate the situation of the IDPs. An appropriate strategy of control of the transmission of cholera and emergency medical intervention can help alleviate the devastating effects. The management of cholera transmission include the supply of sufficient water sources, adequate sanitation, and a public health campaign to maximize the effects of these measures. One key health system challenge that could limit the effectiveness of the interventions would be the people. This paper focuses on studying the resultant large numbers of IDPs from the BH conflict, discussing cholera outbreak as a specific health issue, and presenting a focused humanitarian intervention to address this health need.